ISOLATION AND FUNCTIONAL ANALYSIS OF COCONUT PROTEIN SIMULTANEOUSLY WITH VIRGIN COCONUT OIL (VCO) EXTRACTION FROM COCONUT MILK - Akhirunnisa, Rahmaniah
Coconut (Cocos nucifera) is a commodity that has a high number of production, especially in Indonesia as the largest coconut producer in the world. Coconut processing is mainly focused on coconut oil production, such as virgin coconut oil (VCO). The majority production of VCO is done by wet processing method with the addition of precipitant. Coconut processing for VCO extraction produces by-products in the form of coconut skim milk which has not been utilized because of its high water content. Coconut skim milk has a potential protein content, with 35% protein (dry basis), which can be isolated with isoelectric precipitation method as a plant-based protein. Therefore, the aim of this research is to produce VCO and isolate coconut protein powder simultaneously with the determination of the best condition of solvent to raw material ratio and precipitant agent that produce higher yield of VCO and protein with the best functional characteristics. This research varies solvent to raw material ratio (w/w) 1:1 and 2:1 on extraction stage from coconut meal, and type of precipitant agent HCl 0,1 M and CH3COOH 25% on isolation stage from coconut skim milk. The amount of coconut protein powder is measured by Kjeldahl analysis. Functional characteristics of coconut protein powder including emulsification and foaming properties are then being analyzed. The result of this research shows that increasement of solvent to raw material ratio leads to the yield decreasement of VCO with the value ranged between 50-85 g VCO/100 g coconut meal oil, however it leads to the yield increasement of coconut protein with the value ranged between 30-46 g protein powder/g skim milk protein. Therefore, solvent to raw material ratio 1 (w/w) is the optimum condition to produce high yield of both VCO and coconut protein. Meanwhile, the addition of HCl as precipitant results higher yield of coconut protein than CH3COOH. Neither the difference of solvent to raw material ratio nor precipitant have significant effect to functional characteristics of protein including emulsification and foaming properties.